Functional and logic programming : 13th International Symposium, FLOPS 2016, Kochi, Japan, March 4-6, 2016. Proceedings /: 13th International Symposium, FLOPS 2016, Kochi, Japan, March 4-6, 2016. Proceedings. (2016) - Unknown
No abstract available